Statistical analysis on Moldex Products, Inc. - Baterina, Eunessa A.; Ko, J-Za A.; Salvatierra, Michelle Rae B. (Diliman, Quezon City College of Engineering, 2001)
Moldex Products, Inc. is a major producer of plastic products in the country. The company manufactures products such as polyvinyl chloride (PVC) pipes and fittings, polyethylene pipes and fittings, polybutylene tubings, and rigid PVC films and sheets. Being a participant in the highly competitive plastic manufacturing industry, Moldex aims to continually improve its performance to maintain and increase its market share. One important factor is to improve its manufacturing processes, particularly that of the PVC film production. Critical steps for improving the production process are problem analysis and statistical analysis. Methods engineering tools such as the check sheet and the Ishikawa diagram were used in identifying the problems encountered in production. It was determined that bubbles and fisheyes in the film are the defects that occur with the highest frequency. Major processes breakdown occurs when processed film stick to the main rolls. The principles of experimental design were applied to the process to identify factors crucial to the acceptability of PVC films. Common causes of the main problems determined are the temperature and the speed of the main rollers. From the statistical tests conducted on the two sets of data, from the two parameters, roller temperature and rollers speed, respectively, it was hypothesized that the data are random about the desired thicknesses. This was confirmed through the Runs test for Randomness. The Goodness of Fit test was conducted in order to confirm that the theoretical normal distribution is also the actual distribution of both sets of data. Prior to conducting the design of experiment, it was found out that, at 95 percent confidence, a minimum of five replicates is required for both experiments. The group gathered 25 replicates per treatment in both experiments to ensure minimal error. With the use of One-Factor Fixed Effects Design at six levels, it was determined that the temperature and speed of the rollers affect the thicknesses of the films. These parameters are controlled by the operators. It is therefore recommended that operators strictly monitor these and insure that it falls within the recommended machine parameters. The proper setting of temperature and speed will minimize variations from the desired thickness of the film. It will also minimize rejections due to physical defects. The implementation of the preceding recommendations will ensure the improvement of the PVC film manufacturing process and consequently, it will promote total customer satisfaction.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics